Bench studies of a small axial pump for implantation in patients with low anthropometry - A. S. Buchnev; A. P. Kuleshov; A. A. Drobyshev; V. A. Elenkin; G. A. Shevchenko; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
Objective: to conduct bench tests and determine the working range of the pump speed for an implanted left ven- tricular bypass system aimed at diagnosing and treating patients with low anthropometric status.Materials and methods. The axial pump was investigated using a custom-developed hydrodynamic test bench simulating the cardiovascular system. The bench included systems for pressure and flow measurement and registration, along with software for processing both technical and biomedical parameters.Results. The operating range of the rotor speed for the STREAM CARDIO pump required to achieve a flow rate of 2.5 ± 0.5 L/min at a pressure drop of 80 ± 5 mm Hg is 8000 ± 1000 rpm, with a power consumption of 6.5 ± 1 W.